The future environmental and health impacts of coal - Finkelman, Robert B.; Wolfe, Amy; Hendryx, Michael S. (Energy Geoscience, 2021)
In the United States, coal consumption in the last 12 years has declined from 1,045,140 million short tons in 2007 to 539,420 million short tons in 2019, a decrease of almost 50%. During that period the number of electric power coal generators has declined from 1,470 to 738 accounting for 21% of capacity. An even more dramatic decrease in coal use has occurred in Western Europe. This significant reduction in coal use and the concomitant closure of coal mines and coal-burning power plants will result in substantially cleaner air, reductions in respiratory problems such as asthma, less heart disease, fewer hospitalizations, and other health benefits, as well as a reduction in occupational health problems such as silicosis and Coal Workers’ Pneumoconiosis (Black Lung Disease). However, in China, India, Russia and in several other Asian countries some projections indicate an increase in coal production and use. In some situations, the coal is burned in old, highly polluting power plants. In these regions the health impacts of coal use could worsen. In addition, millions of people in these regions still burn coal in their homes resulting in maximal exposure to the pollutants such as arsenic, selenium, fluorine, and mercury released from coal combustion. [Display omitted] •Impact of coal mining and coal use on Future Environmental and Health Impacts.•Positive and negative impacts and of the dynamic changes in coal mining and use.•Dramatically different approaches of coal mining and use in different parts of the globe.